Fostering Listening Comprehension through Total Physical Response - Indah Werdiningsih; Binti Ainul Mardiyah (ELLITE, 2019)
EFL Learners’ distress in listening to English records in the classroom is one of the matters commonly discovered in Indonesian middle scholars. Listening activities bring students to the mastery of other skills; speaking, writing, and reading. Total Physical Response was created to enhance the students’ ability in listening to a spoken foreign language discourse by giving a physical response when they hear aparticular command. This study works toward finding the effect of Total Physical Response utilization on students’ listening comprehension at MTs Negeri 4 Banyuwangi.The samples of this study were two groups of students; 30 students of VII A and 30 students of VII B. Class VII B was assigned as the control group, while Class VII A as the experimental group where both pre-test and post-test were conducted to each group. The experimental group was taught by using TPR, while in the control group learning is carried out in the way teachers normally teach, that is using Three-phase technique.The hypothesis was tested using independent sample t-test and analyzed by using SPSS. Total Physical Response could administer some refinement on students’ listening, which is evidently manifested in the result of the post-test. Students in experiment group achieved better score than those in control group. This study suggests the use of Total Physical Response to the early middle scholars as an alternative to other teaching methods.